Prostitusi Daring: Antara Kemajuan Teknologi dan Dampak Sosial - Daniello Rudolf Laukon; Lidya Fadila; Naylla Rachma Edhisty; Zahra Hasna Solihat; Siti Hamidah (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2024)
Digital prostitution is an activity that involves the use of the internet to direct someone to prostitution or digital prostitutes. Because of the very easy and free access, and the existence of websites or forums that specifically focus on the world of online prostitution. Society needs to be aware of the normalization and glamorization of digital prostitution in online culture that can undermine healthy views and values regarding sexuality and relationships. Our research method uses the System Literature Review (SLR) research method. It is important for the government and society to work together to create effective regulations and adequate protection for sex workers. Education and awareness about the risks and social impacts of digital prostitution also need to be improved. It is important to change perceptions and values relating for human integrity and dignity. It has negative impacts on the individuals involved, such as damaging their physical and emotional health, spreading sexuality transmitted diseases, and hindering educational and career opportunities. There are social impacts including the objectification of women and a decline in moral values. The demand for illegal sexual services can also contribute to human trafficking and sexual exploitation of children.